CompTIA mobility+ certification Exam guide (Axam mb0-001) - Rogers, bobby E (India mc grow hill education, 2014)
complete coverage of all exam objectives - ideal as both a study tool and an on-the-job reference - filled with practice exam questions and in-depth explanations
All in one is all you need
1
Keywords: Telecommunications engineers certification; computer network; computer technicians; computing technology industry association